EVALUATION OF THE IMPLEMENTATION OF THE AGILE EDUCATION FRAMEWORK IN DEVELOPING STUDENTS' ACADEMIC RESILIENCE AT PKBM FLEXI SCHOOL - Vina Maysari; Amelia Vinayastri; Sigit Muryono (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Currently, there has been no comprehensive evaluation of the effectiveness of the framework's implementation in developing students' academic resilience. This study aims to evaluate the application of the Agile Education Framework in developing students' academic resilience at PKBM Flexi School through the CIPP (Context, Input, Process, Product) evaluation model. This study is a qualitative study involving several evaluation subjects such as the principal, teachers, and students. The study was conducted at PKBM Flexi School, Tangerang, Indonesia. Data collection techniques included interviews. Data were validated by triangulation of techniques and sources. Data were analyzed using interactive analysis through data reduction, data presentation, and drawing and testing conclusions. The results of the study indicate that the first component of the context indicates that the implementation of the Agile Education Framework in PKBM Flexi School has a strong philosophical, regulatory, and institutional foundation. The second component of the input indicates that the readiness of human resources, facilities, and funding at PKBM Flexi School to support the implementation of Agile Education. The third component of the process in the implementation of the Agile Education Framework in PKBM Flexi School shows a dynamic, adaptive, and student-centered learning process. The fourth component of the product shows that the implementation of Agile Education has a significant impact on the development of students' academic resilience. Overall, the evaluation of the implementation of the Agile Education Framework has a positive contribution to the development of students' academic resilience.